2016
DOI: 10.1016/j.jpowsour.2016.03.012
|View full text |Cite
|
Sign up to set email alerts
|

Pr4Ni3O10+δ: A new promising oxygen electrode material for solid oxide fuel cells

Abstract: International audienceThe present work is focused on the study of Pr4Ni3O10+δ as a new cathode material for Solid Oxide Fuel Cells (SOFCs). The structural study leads to an indexation in orthorhombic structure with Fmmm space group, this structure being thermally stable throughout the temperature range up to 1000 °C under air and oxygen. The variation of oxygen content (10+δ) as a function of temperature under different atmospheres show that Pr4Ni3O10+δ is always oxygen over-stoichiometric, which further sugge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
41
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 68 publications
(48 citation statements)
references
References 29 publications
6
41
1
Order By: Relevance
“…Promising electrochemical properties of the PNO end member (x = 2.0) are undermined by poor chemical stability at elevated temperatures corresponding to SOFC operating conditions. [10][11][12][13][14]18 The monoclinic distortion and supercell ordering seen at ambient temperature here may therefore reflect a highly strained structure that readily decomposes to more thermodynamically stable compositions.…”
Section: Structure and Property Trends In La2-xprxnio4+δmentioning
confidence: 85%
See 1 more Smart Citation
“…Promising electrochemical properties of the PNO end member (x = 2.0) are undermined by poor chemical stability at elevated temperatures corresponding to SOFC operating conditions. [10][11][12][13][14]18 The monoclinic distortion and supercell ordering seen at ambient temperature here may therefore reflect a highly strained structure that readily decomposes to more thermodynamically stable compositions.…”
Section: Structure and Property Trends In La2-xprxnio4+δmentioning
confidence: 85%
“…Under oxidizing atmospheres at elevated temperatures, it has been shown that Pr2NiO4+δ can decompose to a mixture of Pr4Ni3O10, PrNiO3-δ, and PrOx. [10][11][12][13][14] For this reason, there has been recent interest in mixed PNO-LNO compositions which could offer a compromise of chemical stability and electrochemical performance. [15][16][17][18][19] However, despite investigations spanning three decades, the phase diagram of the La2-xPrxNiO4+δ system; as a function of composition, oxygen stoichiometry, and temperature, is still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, these compounds show good electronic conductivity [25,26] and high diffusivity of oxide ions [27][28][29]. Then, due to their large anionic bulk diffusion (D*) as well as surface exchange coefficients (k*), combined with good electrical conductivity and thermal expansion properties matching with those of electrolyte materials, they have been extensively used as oxygen electrodes in Solid Oxide Cells [30][31][32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%
“…Layered Ruddlesden-Popper (RP) nickelates with the generic formula (LnNiO 3 ) n LnO (Ln ¼ La, Pr, Nd; n ¼ 1, 2, 3) have attracted considerable interest for potential application as the cathode for intermediate-temperature solid oxide fuel cells (IT-SOFCs). [1][2][3][4][5][6][7] Their crystal structures can be viewed as a stack of one rock-salt LnO layer with a nite number (n) of perovskitetype LnNiO 3 layers along the principal crystallographic axis.…”
Section: Introductionmentioning
confidence: 99%
“…13 However, such a trend was not observed in a comparative study on symmetric cells by Woolley et al 34 Sharma et al 3 showed that La 3 Ni 2 O 7Àd would be a better cathode material than La 4 Ni 3 O 10Àd based on ASR data of symmetric cells using GCO (Ce 0.9 Gd 0.1 O 2Àd ) as the electrolyte. Increasing the order n of the RP nickelates promotes electrical conductivity and long-term stability in the range 600-800 C. 4,13,33,35 Apart from material composition, the microstructure of the cathodes is found to play a key role in their performance. 4,36 In this work, the structure, oxygen nonstoichiometry, electrical conductivity and oxygen transport of Ln…”
Section: Introductionmentioning
confidence: 99%